Systematic review on research trends on sensor-based leak detection methods in water distribution systems - Talhah Mohamad Shirajuddin,; Nur Shazwani Muhammad,; Jazuri Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2022)
A substantial amount of treated water is lost every year due to leakages in water distribution systems. Leakages can be identified and reduced using leakage detection methods, which can be broadly split into computer-based and sensor-based methods. This systematic review focuses on trends in sensor-based leakage detection methods published between 2000 and 2019, following the methodology proposed by PRISMA 2009 (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). We conducted a database search using Scopus, obtaining a total of 78 relevant article papers. We categorized the articles based on the primary leakage detection methods discussed, yielding 33 article papers on acoustic methods, 31 article papers on non-acoustic methods, and the remaining article papers on wireless sensor networks (WSN). The highest number of article papers were published in the “Journal of Sound and Vibration”. Between 2000 and 2007 we observed that acoustic leak detection methods were the most widely researched methods within the published literature. After 2008, non-acoustic leak detection methods became more prominent, subsequently followed by an increase in research focusing on WSNs. During the transition period between acoustic methods and WSNs, non-acoustic leak detection methods started to emerge, showing promising results in detecting leakages. Research interest in WSNs substantially increased in 2016. The application of WSN methods for leakage detection shows a promising advancement in sensor-based leakage detection methods and opportunities for improvement in the future.